STUDI PENGARUH PENGGUNAAN BAHAN FIKSASI AL2(SO4)3 TERHADAP KULIT DOMBA YANG DISAMAK MENGGUNAKAN BAHAN PENYAMAK DARI TANAMAN GAMBIR (UNCARIA GAMBIER) - Prasetyo Hermawan; Elis Nurbalia (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2019)
The purpose of this research was to study of the use of Al2(SO4)3 as fixation agent in taning sheep skin using tanin derived from gambier plants (uncaria gambir). A total 18 pieces of sheep skin were used using Al2(SO4)3 which was varied, ie; 0%, ½%, 1%, 1,5% and 2%, as a control 0,5% H2C2O4 is used. The physical characteristics of the liquid and the leather product were then tested and the test results were compared with the standard lining skin (SNI 06-0237-1989). Addition of 0,5% Al2(SO4)3 reduced the final pH of the fixation liquid from 5.43 to 3.99. The increase in skin thickness at the addition of 0.5% Al2(SO4)3 was 4.14% and in the control test was 5.29%. Skin shrinkage temperature increased from 60,50 0C to 73,17 0C at the addition of 1% Al2(SO4)3. Tensile strength and elongation tended to decrease with the increase in the amount of Al2(SO4)3, but all the results of tensile strength met with SNI because it is above 75 kg/cm2. Tear strength and oil contains of skin tended to decrease with the increase in the addition of Al2(SO4)3. The degree of tanning and tannin content of the skin tended to rise, at the addition of 0.5% Al2(SO4)3 the skin had a degree of tanning 55.23% and a tannin content of 24.66%. SEM test results showed the surface morphology of the skin became even and denser.